Analysis of basic hair cutting skills in cosmetic education students - Sari, Dian Maya; Fauzani, Asrah Reski (Edukasi, 2023)
This research adds to the understanding of skill development in cosmetology education, particularly in a university setting. It highlights the importance of practical, hands-on training and the need for continuous practice to refine and perfect basic cosmetology skills. This study aims to determine the ability to practice basic hair cutting among Medan State University Cosmetology Education students. This research is descriptive. The research population was 30 students. The type of research instrument used was an observation sheet regarding basic hair-cutting practice skills. Observations were carried out by 3 observers who are experts in their fields. The indicator of accuracy in the preparation of tools and work equipment obtained 73% in the good category. The indicator of accuracy in using hair scissors received 60% in the adequate category. The accuracy indicator makes the trimming pattern line get 43.3% in the sufficient category. The indicator for pruning parts obtained 63.3% in the good category. The indicator taking the pruning section obtained 60% in the sufficient category. The pruning result indicator obtained 53.3% in the sufficient category. The timeliness indicator obtained 66.7% in the good category. From the results of observations of basic hair trimming for cosmetology education students at Medan State University, it can be concluded that the average basic hair trimming ability is 60% in the sufficient category. Therefore, it is hoped that students will practice cutting hair more often so that they have good skills and abilities in basic trimming. This study uniquely focuses on the basic hair-cutting skills of Cosmetology Education students at Medan State University, employing detailed assessment indicators and expert observations to provide a comprehensive skill evaluation. Its findings offer novel insights into the effectiveness of practical training in cosmetology education, highlighting areas for improvement and future research directions.